Feasibility of glycated haemoglobin target-setting in adults with diabetes: A mixed-methods study - Samuel J. Westall; Simon Watmough; Ram Prakash Narayanan; Greg Irving; Kevin John Hardy (PLoS ONE, 2026)
Background HbA 1c targets guide diabetes management to reduce complications, yet their psychological effects are poorly understood. This feasibility study evaluated the practicality of conducting a definitive trial evaluating the impact of explicit HbA 1c target-setting in adults with diabetes. Methods We conducted a randomised mixed-methods feasibility study. Adults with diabetes were allocated 1:1 to receive an explicit HbA 1c target set 5 mmol/mol above (Group A) or below (Group B) their current HbA 1c . Biomedical (HbA 1c , blood pressure, BMI) and psychometric patient-reported outcomes were measured at baseline and 3 months. Quantitative data were analysed in SPSS using independent-sample t-tests or Mann–Whitney U tests for between-group comparisons, and paired t-tests or Wilcoxon signed-rank tests for within-group changes. Qualitative data from semi-structured interviews with patients and healthcare professionals were analysed using the Framework Method of thematic analysis in NVivo. Acceptability was assessed via interview, and mixed-methods findings were integrated through triangulation to enhance validity. Results Fifty participants were recruited; 34% withdrew. Though not powered to determine statistical significance, no between-group differences were observed in HbA 1c or patient-reported outcomes. Across groups, diabetes distress decreased, self-efficacy improved, and HbA 1c improved. Interviews indicated high acceptability and identified key motivators (target achievability, hypoglycaemia avoidance) and demotivators (limited understanding, perceived unattainability). Discussion A randomised mixed-methods approach to HbA 1c target-setting is feasible and acceptable, providing methodological insights for a definitive trial. Trial registration The study is registered with the ISRCTN (registration number: 12461724; date registered: 11 th June 2021).